2021
DOI: 10.3390/horticulturae7090273
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Modulation of Controlled Salinity Stress on Morphometric Traits, Mineral Profile, and Bioactive Metabolome Equilibrium in Hydroponic Basil

Abstract: Salinity is a major concern in several ecosystems and has a significant impact on global agriculture. To increase the sustainability of horticultural food systems, better management and usage of saline water and soils need to be supported by knowledge of the crop-specific responses to tolerable levels of salinity. The aim of this work was to study the effects of mild salinity on morphological growth and development, leaf color, mineral composition, antioxidant activities, and phenolic profile of sweet basil (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Concomitant with the decrease in NR activity under salt stress, nitrate content (as a required substrate for NR activity) also decreased in basil leaves. Similar to the results of this research, previous studies have reported a reduction of nitrate in basil leaves under saline conditions (Corrado et al, 2021). The results of this study also showed that salt stress inhibited GS activity and decreased total soluble protein content, limiting nitrogen assimilation under saline conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Concomitant with the decrease in NR activity under salt stress, nitrate content (as a required substrate for NR activity) also decreased in basil leaves. Similar to the results of this research, previous studies have reported a reduction of nitrate in basil leaves under saline conditions (Corrado et al, 2021). The results of this study also showed that salt stress inhibited GS activity and decreased total soluble protein content, limiting nitrogen assimilation under saline conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of the contributions deal with pre-harvest conditions and investigate whether cultivation practices can modulate the yield and nutritional value of vegetable crops and herbs under abiotic stresses. Among these publications, several deal with nutrient supply [2][3][4][5], salinity [6,7], water supply [2,3,8] or lighting conditions [6]. Two manuscripts describe either the effects of applying chemical substances such as gibberellic acid [9] or seaweed extract [10] on the yield and quality of vegetable crops.…”
Section: Special Issue Overviewmentioning
confidence: 99%
“…These crops were mostly grown in greenhouses [2][3][4], but some were grown in an open field [9] or under rain-out shelters [8]. Leafy vegetables and herbs-such as arugula [5], purslane [6] and basil [7]-were used in three experiments and were cultivated in growth cabinets [5,6] or in greenhouses [7]. The bulbs of onions were harvested from plants in a field trial [10], and the asparagus spears for a storage experiment were obtained from local farmers [12].…”
Section: Special Issue Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The need of the processing industry to obtain a product with standardized quality characteristics (i.e., color, aroma, and texture) has resulted in the gradual shift of Genovese basil cultivation from open field to protected cultivation. It is no coincidence that more than 50% of the Italian production of Genovese basil is produced in hydroponics, which guarantees high yields and better nutritional quality, as well as the deseasonalization of the production and the shortening of the production cycle [ 11 , 12 , 13 ]. Trials carried out in collaboration between researchers and producers have elected the floating raft system as the par excellence hydroponic system for the growing of Genovese basil, as it combines simplicity of management and excellent plant adaptability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%